Trade Liberalization and Productivity Growth: A Firm-level Analysis from Kenya - Esaku, Stephen (SSRN, 2020)
We analyze the impact of trade liberalization on firm productivity growth in Kenya’s manufacturing sector, using a panel spanning 8 years; 1992-1999. Our analysis reveals that liberalizing trade generates high productivity improvements in the manufacturing sector. We find that a one-unit reduction in import duties as a percentage of total imports significantly increases firm-level productivity in the manufacturing sector by 5.7%. When we examine this effect on the firm’s share of exported output, we find that lowering of import duties significantly increases the share of output exported by 0.7%. Further, we sought to assess how the effect of import duties varied across the different industries in our sample. Examining the effect of import duties on industrial performance, we find a negative and statistically significant relationship in some of the industries. Our results show heterogeneous effect of reduction of import duties on industrial performance. Not all industries benefited from the lowering of import duties, especially the food and bakery, and garment industry, where productivity did not increase. These findings have important policy implications for improving the manufacturing sector. Consequently, formulating policies that effectively relax restrictive barriers to trade in the economy could speed up firm-level productivity in the manufacturing sector.
Keywords: Firm-Level, Productivity growth, Trade, Trade Liberalization